Muslimah Entrepreneurship and Economic Empowerment in Pengajian - Fadhilah, Ana (Shirkah: Journal of Economics and Business, 2017)
It is a requirement in the practice of economic enterprising to gain productive skill training and capitalization or provision of capital using the moving loan for the member. However, there is still constraint for this method, which is some members are being late to return the loan, because of some reasons. This paper aims to analyze the effect of the moving loan for the pengajian (religious gathering) of An Naml, especially who used it for the food processing business; and to analyze their income’s allocation, whether the income is allocated for the consumption, education, and health or set the income aside for the religious fund, such as infaq, alms, kurban and hajj’s fund. This paper employs qualitative and quantitative approaches, gathering data using in-depth interview, observation and distributing questioners to the 15 select members (purposive sampling). The analysis techniques used are descriptive analysis, paired t-test and correlation analysis. This paper found that the economic enterprise of the member of the An Naml religious gathering, according to the correlation test, proof that between the total income and the savings, before and after the loan given is positively related. In doing so, the connection between the total income and the religious fund before the loan given is related positively, but after the loan given the relation is undetected.Keywords: entrepreneurship, pengajian, economic empowerment